Raziskave stavbarstva in bivalne kulture na Inštitut za slovensko narodopisje - Ledinek Lozej, Špela (Traditiones (Ljubljana), 2001)
The paper is a survey of the research of architecture and housing culture conducted at the Institute of Slovenian Ethnology so far. It encompasses the Slovene Ethnographic Museum's fieldword research, carried out by outside researchers of the former Komisija za slovensko narodopisje (Commission for Slovene Ethnography), typological, historic and monographic studies of periodically settled (mostly by shepherds) dwellings performed after the founding of the Material Culture Section in 1972
Keywords: ethnology; etnologija; stavbarstvo; bivalna kultura; ljudsko slovstvo; oral literature; Slovenia; Slovenija; Inštitut za slovensko narodopisje ZRC SAZU (Ljubljana)